E-GOVERNMENT DAN AKUNTABILITAS SOSIAL Studi Kasus Website “Laporgub!” - Siahaan, Audrey Loemongga Shaloom; Alfirdaus, Laila Kholid; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2025)
LaporGub! is a digital platform that functions as a public complaint channel, designed to provide access to the public in reporting various problems related to public services directly to the local government. This platform is present as part of the e-government initiative to increase public involvement in government and public services. This study aims to analyze in depth how the quality of e-government services provided through the LaporGub! website can affect public involvement in monitoring and evaluating services provided by the government. The quality of service in question includes several aspects, namely efficiency, transparency, and responsibility for services received by the public. Using quantitative descriptive methods, the results of the study show that openness of access to information through the LaporGub! Platform plays a very important role in increasing social accountability. The faster and more responsive the government is in responding to reports given, the higher the public’s trust in the success of e-government in creating good governance. The use of digital technology to bridge interactions between the government and the public as done through LaporGub! Is expected to be a model for similar development platforms in other regions. In other words, LaporGub! Not only functions as a reporting tool, but also as a data source that can provide valuable insights for more responsive decision-making that is oriented towards community needs. This shows that when local governments are able to provide efficient, transparent, and responsive services, community participation will also increase, and public trust in the government will be stronger. These findings are expected to be a reference for local governments in improving and developing more effective e-government platforms for supporting the creation of accountable and participatory governance.